RAS–p110α signalling in macrophages is required for effective inflammatory response and resolution of inflammation - Alejandro Rosell; Agata Adelajda Krygowska; Marta Alcón Pérez; Cristina Cuesta; Mathieu-Benoit Voisin; Juan de Paz; Héctor Sanz-Fraile; Vinothini Rajeeve; Ana Carreras-González; Alberto Berral-González; Ottilie Swinyard; Enrique Gabandé-Rodríguez; et al. (eLife)
Macrophages are crucial in the body’s inflammatory response, with tightly regulated functions for optimal immune system performance. Our study reveals that the RAS–p110α signalling pathway, known for its involvement in various biological processes and tumourigenesis, regulates two vital aspects of the inflammatory response in macrophages: the initial monocyte movement and later-stage lysosomal function. Disrupting this pathway, either in a mouse model or through drug intervention, hampers the inflammatory response, leading to delayed resolution and the development of more severe acute inflammatory reactions in live models. This discovery uncovers a previously unknown role of the p110α isoform in immune regulation within macrophages, offering insight into the complex mechanisms governing their function during inflammation and opening new avenues for modulating inflammatory responses.